2011
DOI: 10.1096/fj.11-193334
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial progesterone receptor exhibits pleiotropic roles in uterine development and function

Abstract: The ovarian steroid progesterone, acting through the progesterone receptor (PR), coordinates endometrial epithelial-stromal cell communication, which is critical for its development and function. PR expression in these cellular compartments is under tight temporal and endocrine control. Although ex vivo studies demonstrated the importance of stromal PR expression, they failed to show a role for epithelial PR in uterine function. Here, the in vivo role of PR in the uterine epithelium is defined using floxed PR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
116
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(124 citation statements)
references
References 47 publications
5
116
3
Order By: Relevance
“…Without functional P4 signaling, as seen in Pgr KO mice, pregnancy is unable to occur because of implantation and decidualization failure (29,30). In our study, the expression of Pgr is significantly decreased in N1ICD OEx mice compared with control mice, which correlates with the dramatic down-regulation of P4 target genes (Ihh, Nr2f2, Areg, Hoxa10, and Hand2) in both epithelial and stromal cells.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Without functional P4 signaling, as seen in Pgr KO mice, pregnancy is unable to occur because of implantation and decidualization failure (29,30). In our study, the expression of Pgr is significantly decreased in N1ICD OEx mice compared with control mice, which correlates with the dramatic down-regulation of P4 target genes (Ihh, Nr2f2, Areg, Hoxa10, and Hand2) in both epithelial and stromal cells.…”
Section: Discussionsupporting
confidence: 48%
“…However, supplemental P4 can only rescue the expression of P4 target genes by 10-30% compared with the expression levels found in control mice. Dysregulated E2 signaling and E2-induced LE proliferation associated with infertility can result from a lack of P4 receptor and target gene expression, including Ihh, Nr2f2, and Hand2 (21,(29)(30)(31)(32). In our study, decreased P4 signaling is associated with abnormally up-regulated E2 signaling in uterine epithelial cells of OEx mice as evidenced by increased expression of Esr1 and its phosphorylated form p-Esr1; up-regulation of target genes Muc1, Muc4, Ltf, and C3; and the increased proliferation of epithelial cells, which is driven by E2 signaling.…”
Section: Discussionmentioning
confidence: 99%
“…While progesterone inhibits estrogen-induced epithelial proliferation, it cooperates with estrogen to promote stromal cell proliferation. Previous studies employing tissue recombination techniques and uterine conditional PR knockout mouse models have demonstrated that both stromal and epithelial PR are required to antagonize estrogen function in the epithelium (Franco et al, 2012, Kurita et al, 1998, Lydon et al, 1995. In mice lacking the PR co-chaperone, FKBP52, uterine receptivity is disrupted due to exaggerated estrogen activity, which resulted from reduced progesterone activity and failure of uterine epithelial differentiation (Tranguch et al, 2005b).…”
Section: Molecular Basis Of Uterine Receptivitymentioning
confidence: 99%
“…In their regulation of physiological events in the uterus, these sex steroid hormones act both cell autonomously and nonautonomously through their TF receptors (1,10). In either case they induce the expression of downstream TFs in the target cell that propagate the initial signal.…”
Section: Ishikawa Cell Proliferation Is Negatively Regulated By Klf15mentioning
confidence: 99%
“…Recent cell-specific gene targeting shows that E 2 induced epithelial cell proliferation is regulated through stromal localized ER (7) that causes the synthesis of paracrine factors, including IGF-1, that act on the epithelial cells (8). PR is required in the uterine epithelium and stroma and causes inhibition of E 2 -induced epithelial cell proliferation (9,10). Despite these cell-specific requirements for the receptor, each hormone induces a cascade of downstream effectors including transcription factors (TF) that propagate the hormonal signal (1).…”
mentioning
confidence: 99%